Comparative Analysis of the Effects of Spectrum and Module Temperature on the Performance of Thin Film Modules on Different Sites - Nofuentes Garrido, Gustavo; García-Domingo, Beatriz; Fuentes, Manuel; Moreno-Sáez, Rafael; Cañete-Torralvo, Cristina; Sidrach-de-Cardona-Ortin, Mariano; Alonso, M. A.; Chenlo, Faustino (My University, 2012)
The electric behavior under natural sunlight of thin film PV modules is more difficult to predict than that of crystalline silicon ones owing to the higher sensitivity to the spectral distribution of the former when compared with the latter, among some other factors. The purpose of this work is aimed at looking into the influence of the spectral irradiance and the module temperature on the outdoor performance of recent commercially available a- Si, CdTe and a-Si/μc-Si modules in sites with different climates in Spain. This paper is addressed to present the results of a 12-month experimental campaign experienced by modules of these thin film technologies carried out in the utilities of the CIEMAT/DER (Madrid, continental climate) and those of the University of Málaga (Málaga, Mediterranean climate). For each one of the tested specimens, contour graphs of their performance ratio (PR) as a function of module temperature and average photon energy (APE) are shown. A strong dependence of PR on APE is noticeable at module temperatures below some 45º C so that as a general trend, the module performance improves as APE increases. However, the tested a-Si and a-Si/uc-Si modules show little sensitivity to module temperature within some specific ranges of values of APE which lie in the vicinity of the APE value for the AM1.5G spectrum. Last, spectral gains achieved at high values of APE together with cold temperatures yield figures of PR above 1 in some cases.
Keywords: Energía solar - Investigación; Test and Measurement; Thin Film (TF); PV Module